ANALYSIS OF THERMAL COMFORT IN A GYM OF PHYSICAL ACTIVITIES: A CASE STUDY (Fiep Bulletin - online, 2013)
The academies became an option in urban centers that offer in the same physical space equipment to exercise the whole body, aerobic activities, martial arts and other services being sought by men and women of various ages, stimulating the practice of physical activities, which has a direct influence on the lifestyle of adults. This metabolic condition combined with a thermally unsuitable environment can generate physiological consequences on users of gyms, such as hyperthermia, dizziness, dehydration, skin diseases, psychoneuroses, cataracts, fainting hypovolemia or sodium deficiency, nausea, irritability and drowsiness. This study aimed to assess the environment of academia Federal University of Technology - Paraná, Campus Ponta Grossa, through the thermal point of view, and applying the method of Predicted Mean Vote (PMV), standardized by ISO 7730 (2005). The results showed that all areas of the gym are inadequate from the standpoint of heat, so that PMV values ??were obtained ranging between 2.3 and 2.8, which according to the scale of thermal sensation, are characterized between "Hot" and "Very Hot". At the end of their activities, users of academia were invited to answer a questionnaire regarding the environment of the academy, and the conclusion was that 82.14% of users want the temperature to be reduced so that they can perform their physical activities in a comfortable thermal point of view.
Keywords: Gym; Thermal Comfort; Physical Activity.